Conditions for the Group of Military Personnel Determine the Results of Their Activities in Combat Situations or Combat Situations (Eurasian Journal of History, Geography and Economics, 2023)
This article mainly considers the conditions under which the group of military personnel will be located, as well as the results of this group's activities in specific combat situations or combat situations.